Material Ecocriticism - Oppermann, Serpil; Iovino, Serenella, 1971- (Book collections on Project MUSE., 2014)
"Ecocriticsim is the study of literature and the environment from an interdisciplinary point of view, coming together to analyze the environment and determine possible solutions for the correction of the contemporary environmental situation. The discipline was heralded by publication of The Ecocrticism Reader (U Georgia, 1996) and Lawrence Buell's The Environmental Imagination (Harvard, 1995). Recently, all kinds of "texts" have been subjected to ecocritical methods (film, TV, scientific narrative, and architecture as well as nature writing and Romantic poetry) and questions about place (see our Getting Back into Place, 2nd ed., 2009), materialism (agency, process, and relationship), grounding in the natural sciences, and philosophical precision have defined the movement. This edited volume aims to bring ecocriticism closer to the material turn. The essays collected here focus on material entanglements, the agency of things, processes, and making meaning out of matter and things. It is an effective an broad-ranging reflection on contemporary human experience and human expression about the world to which we are intimately connected. Boith Iovino and Opperman are well know as ecocrtical theorists. They have collected essays from many of the stars in the discipline and this volume should set a new benchmark for the field"--